(untitled) (El Hilo de la Fabula, 2022)
The research focuses on the so-called political theater of Dario Fo and Franca Rame, conceived as a narrative tool of the Years of Lead. The following research aims to clarify the content of the investigative theater definition suggested by Dario Fo and Franca Rame (who always considered the term “political theater” redundant) through unpublished sources, highlighting the investigative work that Fo and Franca carried out day after day on the facts that shocked Italy during those years.